Intensive Class Training Model for Developing Lecturers’English Competence at IAIN Imam Bonjol Padang - Darmayenti, Darmayenti; Nofiadri, Nofel (AT-TA'LIM, 2016)
Research and Development (RD) project was used to develop lecturers’ English competence particularly on speaking and writing at State Institute of Islamic Studies of Imam Bonjol Padang.  The lecturers need to develop their competence in English in order to prepare themselves to add new information of lecturing materials and writing papers. Borg and Gall’s steps were used to develop the model. Twenty active lecturers who had s2 and s3 program, who were randomly selected, participated on this research. During the process of the research, observation, questionnaire, and TOEFL test, speaking and writing tests were used to collect the data. The experimental research type and one group pre test- post test design were used to conduct the research. The result of the research showed that 74% of respondents need intensive class training model to develop their English competence. The implementation of intensive class training model gave a significant effect toward lecturers’ English competence. It is concluded that this model is more effective to improve lecturers’ on English competences. Therefore, it is recommended that this model can be implemented at IAIN Imam Bonjol Padang in order to develop lecturers’ English competences and to enhance the quality of lecturers.